Polityczność zbrodni? Hermeneutyczna teoria śladu w kryminałach = Politics in crime? Hermeneutical theory of clue in crime novels - Regiewicz, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Considering the popularity of retro crime novels, it can be said that the past is one of crucial social aspects in the contemporary cultural narration. The analysis of crime novels undertaken in this article, however, touches upon narration which is encapsulated in the concept of post-traumatic literature. By employing the hermeneutical theory of clue as a tool for shedding light on the past, we study the impact of historical events (both of the great History and the smaller, individual one) on the contemporary discourse of identity. The observations lead to the conclusion that the discourse of social hatred is more and more vividly constructed and embodies in various aspects of life.
Keywords: powieść kryminalna retro; teoria "śladu"